2019
DOI: 10.1111/pde.13774
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopic findings of umbilical granuloma

Abstract: Dermoscopic findings in umbilical granuloma are vascular polymorphism comprised of linear irregular and arborizing vessels with structureless areas distributed over a milky-red background. The increase of angiogenesis and neovascularization is represented by the linear irregular and arborizing vessels. Structureless areas over an irregularly milky-red background are originated by the proliferation of vascular endothelial cells and fibroblasts, with capillary and granulation tissue formation. Pediatric Dermatol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The systematic review revealed two cases of umbilical granuloma. Both of them (2/2; 100%) presented with a polymorphic vascular pattern and a milky-white background, corresponding with the presence of granulation tissue and the proliferation of vascular endothelial cells and fibroblasts [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The systematic review revealed two cases of umbilical granuloma. Both of them (2/2; 100%) presented with a polymorphic vascular pattern and a milky-white background, corresponding with the presence of granulation tissue and the proliferation of vascular endothelial cells and fibroblasts [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The following supporting information can be downloaded at: , Table S1: Joanna Briggs Institute Appraisal tool questions; Table S2: Risk of bias assessment; Table S3: Overview of the characteristics of included studies. References [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ] are cited in the Supplementary Materials.…”
mentioning
confidence: 99%
“…It is the most common umbilical abnormality found in infants, occurring in one in 500 newborns [ 1 ]. The overgrowth is associated with fibroblasts, pro-inflammatory and inflammatory cells, and endothelial cells, all embedded in edematous stromal tissue [ 2 ]. The presentation is a small nodular growth located at the base of the umbilicus.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings were similar to previous reported dermatoscopic findings of UG by Ancer-Arellano J et al . [ 2 ] Patient was treated with topical application of 30% trichloracetic acid once a week followed by resolution of the lesions. Other known treatment options include topical silver nitrate, table salt application and surgical excision.…”
mentioning
confidence: 99%